THE EFFECT OF CELERY LEAF DECOCTION ON BLOOD PRESSURE REDUCTION IN HYPERTENSION PATIENTS IN THE BANE PEMATANGSIANTAR UPT HEALTH CENTER WORK AREA IN 2021 - Richard Fredrik Marpaung; Pinondang Hotria Siregar (RADJA PUBLIKA, 2022)
Hypertension or often called high blood pressure is a disease of the heart or blood vessels characterized by increased blood pressure. This type of research uses a Quasy Experiment Design with a one group pretest-posttest approach. The population in this study were all patients with hypertension at the UPT Puskesmas Bane. The sample in this study was 30 patients with hypertension using total sampling technique. Data was collected by measuring blood pressure before and after intervention with a sphymomanometer. The statistical test used was the T test, for the results of the study showed changes in blood pressure with a significant value = 0.000 <0.05, then there was an effect of boiled celery leaves on reducing blood pressure in patients with hypertension at UPT Puskesmas Bane Pematangsiantar. Based on the results of the study, it was found that there was a change in blood pressure in patients with hypertension after being influenced by giving boiled celery leaves for approximately 14 days so that giving celery leaf decoction was effectively used as non-pharmacological therapy for patients with hypertension.